Constituintes químicos de Vellozia plicata Mart.: caracterização, estudos in silico e avaliação do potencial anti-HIV-1 - Pinheiro, Anderson Angel Vieira (2020)
Natural products have historically been used to treat a variety of health threats and are a potential source for bioactive drugs. In this perspective, a re-study of Vellozia plicata Mart. was carried out. with the objective of isolating compounds, quantifying a chemical marker, evaluating, through studies in silico, with probability of anti-HIV activity of compounds, as well as predicting their risks of cytotoxicity, oral, intestinal absorption rate and hepatic metabolism. In addition, it investigated the cell viability and anti-HIV-1 activity of compounds and ethanolic extract. In this phytochemical study there were three compound compounds, among them amentoflavone (9), 3',8''- biisocampferide (10) and 3'-apigenin-8' '- isocaempferide (11), the latter being listed for the first time in literature. Compound (9) was proposed as a chemical marker of the species, quantified in 106.92 μg/mg of crude extract of V. plicata, with a standard deviation of less than 5%, as recommended by Resolution 899/2003 of the National Health Surveillance Agency. Biflavonoids were predicted using KNIME for the potential probability of biological activity (HIV-1), an oral absorption index and the toxicological parameters of mutagenicity and carcinogenicity. They described the ABS percentage higher than the control (36.60%) and no toxicity risks were observed within the parameters analyzed by the OSIRIS software. Predictive estimates of intestinal permeability and absorption of the three biflavonoids are >50% probable. The compounds demonstrated good MolDock Score results in molecular docking, with a better interaction between compound (9) with a protease and (10) with an integrase and reverse transcriptase. The three compounds had their structures predicted after hepatic metabolism, which include metabolic pathway in the liver to (9), if aromatic hydroxylation of cytochrome P450 enzymes has already been performed (10) and (11) greater expression of some groups has occurred aromatic and aliphatic by O-desalination, hydroxylation and carboxylation. The compounds generated from the metabolization of (9), (10) and (11) were predicted, using OSIRIS, regarding the mutagenicity and carcinogenicity capacity, however, only (9) presented a score of 29.95%, demonstrating high risk of mutagenicity. Among the compounds tested in biological studies, ethanol extract of V. plicata (71.19%) and amentoflavone (70.98%) found better cell viability compared to uninfected JLTRF - R5 cells. In assessing the anti-HIV-1 potential, no significant difference was observed between the positive control (100% DMSO), biflavonoids and ethanolic extract. In this perspective, this study demonstrates the chemical potential of V. plicata and demonstrates predictive pharmacokinetic information for biflavonoids that may assist in the process of investigation and / or development of future drugs. In addition, it highlighted the need for further investigations using other methodologies or the use of other positive controls to assess the anti-HIV-1 potential.